Women's Ecological Agency in Robert Frost's Selected Poems: An Ecofeminist Study - Agung Suhadi; Sarwit Sarwono (Teaching English and Language Learning English Journal, 2026)
This study examines the representation of women's ecological agency in Robert Frost's selected poems through Karen J. Warren's ecofeminist philosophy. This study investigates how feminine figures and feminized natural elements function as ecological subjects in Spoils of the Dead, The Tuft of Flowers, Wind and Window Flower, Gathering Leaves, and Asking for Roses. Employing a qualitative descriptive design, the research uses thematic textual analysis based on Warren's concepts of hierarchical dualism, the logic of domination, ecological ethics, and the ethic of care. The findings reveal Frost constructs women's ecological agency through four interrelated roles: ecological guidance, ethical mediation, environmental stewardship, and respectful negotiation with nature. He presents them as active ecological mediators who foster care, reciprocity, conservation, and contextual responsibility. Shortly, Frost's poetry advances an ecofeminist vision in which sustainable human nature relationships are achieved through ethical coexistence rather than domination. These findings enrich ecofeminist literary criticism by highlighting women's transformative roles in promoting ecological harmony and environmental responsibility.